The five phases of pole vault performance - Petrov, V. (3rd European Pole Vault Conference - Köln 2008, 2008)
Vitali Petrov first explained the fundamental principles of modern pole vault technique in the five phases start, runup, takeoff, swing-inversion and bar clearance from his point of view. Based on biomechanical data, picture sequences and video clips of some of the world best vaulters he then discussed individual deviations from these principles. His general critique on the world top male vaulters focused on their inferior abilities to generate enough runup speed and perfect preparation of pole plant and takeoff due to the fact that their typical runup length shortened from (typically) 20-22 steps during 1985 to 1995 to 16-18 steps nowadays. Finally he gave his views on individual training strategies for developing young athletes in the German national team.